A new mid-Cretaceous Neomeris (dasycladacean alga) from the Potiguar Basin, Brazil - Granier, Bruno; Dias-Brito, Dimas [UNESP]; Bucur, Ioan I. (Springer Nature, 2013)
Neomeris (Lamouroux, 1816) is an extant taxon, the origin of which can be tracked back into Early Cretaceous times. The introduction of a new mid-Cretaceous species from Brazil, i.e., Neomeris srivastavai n. sp., offers the opportunity to review the subdivision of the genus into three subgenera, to complete the catalogue of the fossil calcareous algae of Brazil, and to point out the huge stratigraphic gap and lack of documentation between the first occurrence of the dasycladacean model of reproduction, i.e., choristospory, and the oldest record so far known of an undescribed fossil Neomeris (from Portugal). © Springer-Verlag Berlin Heidelberg 2012.
Keywords: Choristosporate; Cretaceous; Dasycladaceae; Dasycladales; Neomeris; alga; biostratigraphy; fossil; fossil record; new species; species occurrence; taxonomy; Brazil